Difference In Clinico - Etiological Profile of Neonatal Hyperbilirubinemia at A Tertiary Care Hospital (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Neonatal hyperbilirubinemia is one of the most common conditions requiring medical attention in the neonatal period. While most cases are physiological, delayed diagnosis and inappropriate management can lead to severe complications, including acute bilirubin encephalopathy and kernicterus. Aim & Objectives: To compare the clinico-etiological profile of neonatal hyperbilirubinemia between inborn and outborn neonates admitted to a tertiary care hospital and to identify key risk factors associated with pathological jaundice. Material & Methods: This hospital-based cross-sectional study was conducted in the Special Newborn Care Unit (SNCU) of a tertiary care hospital in Greater Noida over 12 months. Enrolled patients included 360 neonates ≤28 days with hyperbilirubinemia, either clinically suspected or biochemically confirmed. Data collection was done using a structured proforma, and etiological diagnosis was determined based on clinical and laboratory findings. Statistical analysis was done using SPSS v28.0; Chi-square and independent t-test were employed, with significance confirmed at p